Strategies And The Role Of Teachers In Developing Inclusion Curriculum For Children With Special Needs - Farida Isroani; Agus Maimun; Ahmad Barizi (Cita konsultindo, 2025)
Education is a process of humanizing humans that must be adapted to the situation and conditions as well as the development of the times. In addition, the definition of Education according to Law No. 20 of 2003 concerning SISDIKNAS, is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills they need. Inclusive education is an approach to education that recognizes the right of every individual to receive a quality education, regardless of their differences or special needs. Inclusive education has emerged as a response to challenges, with a vision to create a welcoming, supportive and equitable learning environment for all students. Inclusive education is not only about including students with special needs into regular classrooms, but also about changing the culture and practices of education as a whole. It involves the collaborative efforts of all education stakeholders, including teachers, school staff, parents, and communities, to create an inclusive environment and promote educational equity.